Autonomous region formation in the Middle East: cases in Kurdistan - Wipperfurth, Pike James, author; Cavdar, Gamze, advisor; Harris, Peter, committee member; Yarrington, Jonna, committee member (Colorado State University. Libraries, 2024)
Autonomous Region Formation in the Middle East - Cases in Kurdistan, is a thesis paper that interacts with Yash Ghai's theory for the formation of autonomous regions (Ghai, 2003), and applies the analytical framework developed by Yash Ghai and Sophia Woodman (Ghai and Woodman, 2013) to a series of cases left out in the original study. The paper seeks to address the gaps and limitations of the original study by selecting cases from the Middle East geographic region, stemming from the shared experiences of the Kurdish people and their bids for autonomous region formation, and encompass both established and unestablished autonomous units. The cases of Iraqi Kurdistan (Iraq) and the Autonomous Administration of North and East Syria (AANES) (Syria) serve as established autonomous units while the Kurdish majority regions of Bakur (Turkey) and Rojhelat (Iran) serve as unestablished cases for which a comparative analysis can be made. By utilizing Ghai's theory (Ghai, 2003) and the analytical framework of the original study (Ghai and Woodman, 2013), this paper tests the theory and framework against a new set of cases with characteristics different than those in the original study, effectively challenging, testing, and advancing the theory and framework. The paper highlights the strengths and weaknesses of the theory and analytical framework, as well as proposes potential factors and avenues of analysis that could be included in future studies.
Keywords: autonomy; Kurdistan; Middle East politics; Kurd; autonomous region; Middle East and North Africa (MENA)